2018
DOI: 10.1172/jci93090
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage migration inhibitory factor mediates metabolic dysfunction induced by atypical antipsychotic therapy

Abstract: Yale University holds rights to patents that describe the potential utility of MIF inhibition and MIF genotype determination. RB has applied for a patent related to MIF modulators (9540322). RB and LL have applied for a patent related to the method of inhibiting binding or activity of MIF by administering a MIF antagonist (9221903). RB has applied for a patent related to MIF promoter polymorphism in inflammatory disease (9139877).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 54 publications
0
34
1
Order By: Relevance
“…Traditionally, the diagnosis of preoperative LN status in PDAC depends on imaging examinations. Studies have shown that the accuracy of CECT diagnosis for LN metastasis is 48%, and even with 18fluorodeoxyglucose PET/CT, the accuracy is only approximately 68% [38]. In this study, the diagnostic accuracy of CT-reported LN status in the primary cohort was 60, and 68% in the validation cohort.…”
Section: Discussionmentioning
confidence: 54%
“…Traditionally, the diagnosis of preoperative LN status in PDAC depends on imaging examinations. Studies have shown that the accuracy of CECT diagnosis for LN metastasis is 48%, and even with 18fluorodeoxyglucose PET/CT, the accuracy is only approximately 68% [38]. In this study, the diagnostic accuracy of CT-reported LN status in the primary cohort was 60, and 68% in the validation cohort.…”
Section: Discussionmentioning
confidence: 54%
“…After calculations using this software, a total of ~30 adult WT mice and ~30 adult Cd74 −/− mice (both sexes) were used for both in vivo and in vitro studies. Plasma MIF levels were measured using a commercial R&D human MIF kit per manufacturer's instruction (Cui et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…However, opipramol is administered at doses up to 200 mg/day [23,38], making our observations at 1-10 µM relevant. Moreover, risperidone, which induces a modest antilipolytic effect, also modestly increases adiponectin levels in treated patients with schizophrenia, wheraes olanzapine decreases the circulating levels of this insulin-sensitizing adipokine [56] and increases pro-inflammatory cytokines [57]. This allows the supposition that opipramol could also have opposite effects to olanzapine when considering adipocyte functions other than lipolysis and glucose transport.…”
Section: Discussionmentioning
confidence: 99%